Foreign Policy and Area Studies Entangled: A Case Study of the PRC’s Southeast Asian Studies - Kankan Xie (Minerva: A Review of Science, Learning and Policy, 2026)
Chinese universities have actively engaged in knowledge production about other countries and played crucial roles in training professionals for the country’s foreign policy community since the founding of the People’s Republic (PRC). For decades, the transformations of the PRC’s international and area studies programs have not only reflected the shifting demands of top decision-makers but also influenced the interactions among scholars, academic institutions, government agencies, business elites, and the general public. This article analyzes the ups and downs of China’s international and area studies programs in the second half of the 20th century and how they were closely intertwined with the country’s shifting priorities in foreign policy, overseas Chinese affairs, and higher education. Primarily focusing on the case of Southeast Asian Studies (SEAS), this paper explores how the PRC’s area studies programs interacted with the country’s foreign policy during the 1955–1965 and post-1978 periods. Despite the changing geopolitical dynamics after 2000, the academic infrastructure and particular institutional culture formed in these two phases remain essential to our understanding of China’s area studies initiatives today.